Validation of a Questionnaire on Knowledge and Barriers of Breast Milk Expression among Mothers of Premature Infants - Wan Nor, Wan Haiera; Mohamad, Noraini; Saddki, Norkhafizah; Mat Yudin @ Badrin, Zainab; Tengku Ismail, Tengku Alina; Sulaiman, Zaharah; Ibrahim, Nor Rosidah (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to develop and validate a Malay language questionnaire to assess mothers' knowledge in providing breast milk for premature infants, and barriers to breast milk expression while the infants are in the Neonatal Intensive Care Unit (NICU). Two tertiary hospitals in Kelantan, Malaysia participated in this cross-sectional study. Relevant items of knowledge and barriers were identified through a literature search, clinical observations, and expert opinion. Ten breastfeeding experts validated the content of the knowledge and barriers to breast milk expression questionnaire.The effectiveness of the questionnaires was tested for face validity among ten mothers, followed by reliability tests comprising 50 mothers who gave birth prematurely. The 20 knowledge items and 16 barrier items have an Item-level Content Validity Index (I-CVI) of 0.99, indicating good relevance of the knowledge and barrier items. The knowledge and barrier questionnaires had Item-level Face Validity Indexes (I-FVIs) of 1.00 and 0.99, respectively, suggesting clear and comprehensible items. The questionnaires obtained a Cronbach alpha score of 0.726 for knowledge and 0.736 for barriers, showing that they are reliable tools for assessing knowledge and breast milk expression barriers. The validity and reliability of the newly developed Malay version of the questionnaire have been established for evaluating breastfeeding knowledge and barriers to expressing breast milk among mothers with premature infants.